Antibacterial and antifungal alkaloids from Asian angiosperms: distribution, mechanisms of action, structure-activity, and clinical potentials - Mazdida Sulaiman; Khoshnur Jannat; Veeranoot Nissapatorn; Mohammed Rahmatullah; Alok K. Paul; Maria de Lourdes Perei; Mogana Rajagopal; Monica Suleiman; Mark S. Butler; Mohammed Khaled Bin Break; Jean-Frédéric Weber; Polrat Wilairatana; et al. (MDPI, 2022)
The emergence of multidrug-resistant bacteria and fungi requires the development of antibiotics and antifungal agents. This review identified natural products isolated from Asian angiosperms with antibacterial and/or antifungal activities and analyzed their distribution, molecular weights, solubility, and modes of action. All data in this review were compiled from Google Scholar, PubMed, Science Direct, Web of Science, ChemSpider, PubChem, and a library search from 1979 to 2022. One hundred and forty-one antibacterial and/or antifungal alkaloids were identified during this period, mainly from basal angiosperms. The most active alkaloids are mainly planar, amphiphilic, with a molecular mass between 200 and 400 g/mol, and a polar surface area of about 50 Å2, and target DNA and/or topoisomerase as well as the cytoplasmic membrane. 8-Acetylnorchelerythrine, cryptolepine, 8-hydroxydihydrochelerythrine, 6-methoxydihydrosanguinarine, 2′-nortiliacorinine, pendulamine A and B, rhetsisine, sampangine, tiliacorine, tryptanthrin, tylophorinine, vallesamine, and viroallosecurinine yielded MIC ≤ 1 µg/mL and are candidates for the development of lead molecules.